2018
DOI: 10.21323/2618-9771-2018-1-2-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Nfluence of Fat Phase Ontechnologically Important Indicators of Ice Cream Plombir Without Emulsifiers

Abstract: The determination of the technological functionality of milk fat particles in terms of their effect on the nucleation in ice cream plombir with a mass fraction of milk fat of at least 15% was the aim of the study. this work was carried out to justify the possibility of producing ice cream without emulsifiers — components that stabilize the air phase. It has been established that milk fat, with content of at least 15% in the ice cream, as a structural element of the system, positively influences the effective v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In addition, based upon the composition of frozen whipped fruit desserts it is obvious that in their structure less crystallization centers will be formed when hardening in the freezer due to the absence of fatty particles intensifying nucleation [13] as compared with milk ice cream. In such a case lager crystals will be formed in frozen whipped fruit desserts at further freezing in comparison with milk ice cream.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, based upon the composition of frozen whipped fruit desserts it is obvious that in their structure less crystallization centers will be formed when hardening in the freezer due to the absence of fatty particles intensifying nucleation [13] as compared with milk ice cream. In such a case lager crystals will be formed in frozen whipped fruit desserts at further freezing in comparison with milk ice cream.…”
Section: Resultsmentioning
confidence: 99%
“…The sizes of air bubbles and ice crystals were determined with Imagescope M software and their average sizes were calculated. Up to 10 images were obtained and processed in order to increase the accuracy and reliability of measurements for each sample [6,9]. Overrun was determined according to the procedure described in Appendix G of GOST 31457-2012 [10].…”
Section: Methodsmentioning
confidence: 99%
“…The researches of aging process of ice cream mixes are not widely represented in scientific publications. A series of studies has shown the necessity of aging for the ice cream with a high mass fraction of fat of 10%-15%, if the emulsifier is included into the ingredients of the ice cream [2,3,4,5,6], while the type and composition of the fat component (milk fat, milk fat substitute or a combination thereof) provide no profound effect.…”
Section: Introductionmentioning
confidence: 99%
“…The study the state and dispersion of the air phase and ice crystals was carried out by the microstructural method using a CX41RF microscope (Japan) with program control. The sizes of air bubbles and ice crystals were determined, and their average sizes were calculated [15]. For ice crystals, the "angle of curvature" was additionally calculated by determining the value of the angle between the base of the ice crystal and its lateral faces.…”
Section: Study Of the Size And Dispersion Of Air Bubbles And Ice Crys...mentioning
confidence: 99%